Budesonide Enemas for Topical Therapy of Ulcerative Colitis - P Rutgeerts (Canadian Journal of Gastroenterology)
Budesonide is a nonhalogenated glucocorticosteroid that is very suitable for topical therapy in left-sided colitis because it has a high ratio of topical to systemic activity. Although it is absorbed, it is very rapidly metabolized by the liver (first pass metabolism). It does not suppress the hypothalamic-pituitary axis. Budesonide has been shown to be more effective than placebo and predinsolone enemas for the treatment of left-sided ulcerative colitis.